Tuberculosis and diabetes: bidirectional screening and management challenges in South Indian population - Piruthivirajan, Nivedhitha; Keerthi, K. P. Eshwaanth; Maruthupandian; Piruthivirajan, K.; Shanmugam, Murali (International Journal of Research in Medical Sciences, 2025)
Background: The World Health Organization (WHO) and the International Union Against Tuberculosis and Lung Disease have advocated for bidirectional screening testing TB patients for diabetes and vice versa—as a strategic approach to early detection and integrated management. Aim of the study is to evaluate the effectiveness, feasibility, and challenges of bidirectional screening for tuberculosis (TB) and diabetes mellitus (DM), and to identify barriers and opportunities for integrated management of coexisting TB and DM in high-burden settings. Methods: This was a prospective, observational, cross-sectional study conducted to evaluate the implementation and challenges of bidirectional screening for tuberculosis (TB) and diabetes mellitus (DM) in a high-burden tertiary care setting. The study was carried out over a period of three years from February 2022 to January 2025. Results: High undiagnosed DM in TB patients (27.2%) and TB in DM patients (15.3%), underscoring bidirectional screening gaps. TB and DM patients had poorer treatment outcomes (73.5% success vs. 85.7%, *p=0.03*). Systemic barriers: kit shortages (52%) and protocol inconsistencies (44%) dominated challenges. Age >45 and pulmonary TB doubled DM risk (OR>1.8, p<0.02). Conclusions: Our study demonstrated a substantial prevalence of undiagnosed diabetes among TB patients and active TB among diabetic patients, both of which adversely affected treatment outcomes. Bidirectional screening is crucial for early detection, timely intervention, and improved clinical outcomes.